Catch-22: War, Refugees, COVID-19, and the Scourge of Antimicrobial Resistance - Osman, Marwan; Cummings, Kevin J.; El Omari, Khaled; Kassem, Issmat I. (Frontiers in Medicine, 2022)
Wars have hidden repercussions beyond the immediate losses of life, well-being, and prosperity. Those that flee wars and seek refuge in safer locations are not immune to the tragic impacts. Of particular concern is the susceptibility of the refugee populations to infectious diseases and antimicrobial-resistant pathogens. This poses a detrimental risk to these disenfranchised populations, who often have limited access to medical care, sanitation, and nutritious and safe food. Furthermore, antimicrobial-resistant pathogens in refugees can be both transmitted to and acquired from their hosting communities. The latter is particularly problematic when the host countries suffer from serious challenges such as limited resources, pollution, and widespread antimicrobial resistance (AMR). Here, we discuss AMR in refugees of the ongoing Syrian war, a conflict that resulted in the largest population displacement in recent history. We argue that Syrian refugees and their hosting communities are at an elevated risk of complicated and life-threatening AMR infections. We also call on the international community to address this grievous problem that threatens the disenfranchised refugee populations and can spill over across geographic borders to affect multiple countries.